Odor Source Localization Using Optimization Algorithm for Sensor Network with Movable Nodes - Yossiri Ariyakul (My University, 2022)
In this paper, the approach of using optimization algorithm for odor source localization was proposed. The concept uses a number of movable odor robots which comprise of an odor sensor, an anemometer and a wireless communication module to sense the targeted odor. The odor robots construct a movable sensor network by which the measured odor intensity is sent to the processor wirelessly to perform the localization in order to point out the position of the odor source by using optimization algorithm. The odor source localization map is obtained as a result. The map represents the possibility that the odor source is located at any point in the area. The result also implies the direction that the odor robots should move toward to reach the odor source remotely. The proposed method was experimentally evaluated by constructing the odor source localization map using three, four, and five sensor nodes in which the accuracy to predict the position of the odor source can be observed.
Keywords: Insect Pheromone Research and Control; Advanced Chemical Sensor Technologies; Olfactory and Sensory Function Studies